The protein disulfide isomerase code for cell signaling - Laurindo, Francisco R. M. (Henry Stewart Talks, 2023)
Thiol modifications in redox signaling, Protein disulfide isomerase A1 (PDIA1), ER protein folding, PDIA1 effects, Redox potentials of PDIs, PDIA1 and cytoskeleton regulation, VSMC migration and cytoskeletal organization, PDIA1 effect on vascular smooth muscle regulation, PDI/RhoGDI genes